Macromedia Flash MX ActionScript for fun & games - Rosenzweig, Gary (Que, 2002)
Anyone with moderate Macromedia Flash experience who is looking to acquire or improve their understanding of ActionScript will find this book a valuable resource. Author Gary Rosenzweig is highly respected in the Macromedia community and pioneered the use of advanced programming techniques in Macromedia Flash. For this edition, he has updated the games from the previous edition and has added several new projects. Each chapter studies and then deconstructs a new type of game or gadget such as hunt and click games, catch and avoid games, or action and adventure games and the CD contains the project source code.